PENGARUH PUPUK NPK PELANGI DAN PUPUK DAUN GROW TEAM M TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicon esculentum L. Mill) VARIETAS PERMATA - Nanang Saberan, Abdul Rahmi, dan Helda Syahfari (Universitas 17 Agustus 1945 Samarinda, 2014)
Objectives of the research were : (1) to study the effect of NPK Pelangi fertilizer abd Grow Team M foliar spray fertilizer, as well as their interaction on the growth and yield of tomato; (2) to find profer dosage of NPK Pelangi fertilizer and proper concentration of Grow Team M foliar spray fertilizer for better growth and yield of tomato. The research was carried out from January to May 2013, since preparation of growing media until crop harvested. It was held at Melak Ilir Urban Village, Melak Sub-District, West Kutai District. The Completely Randomised Design was employed for this research with factorial 4 x 4 and 4 replications. The first factor was NPK Pelangi fertilizer dosage (N) that consisted of 4 levels: no NPK Pelangi fertilizer application (n0), 125 kg ha-1 equals to 1,25 g polybag-1 (n1), 250 kg ha-1 equals to 2,50 g polybag-1 (n2), and 375 kg ha-1 equals to 3,75 g polybag-1 (n3). And the second factor was Grow Team M foliar spray concentration (D) that consisted of 4 levels: no Grow Team M foliar spray fertilizer application (d0), 1 ml per litre water (d1), 2 ml per litre water (d2), and 3 ml per litre water (d3). Results of the research revealed that: (1) the NPK Pelangi fertilizer affected very significantly on the plant height at 2, 4, and 6 weeks after sowing, days of crop firstly flowered, days of crop harvested, number of fruit per crop, weight per fruit, and fruit weight per crop. The weighest fruit was attained by 375 kg ha-1 equals to 3,75 g polybag-1 treatment (n3), namely 195,83 g per crop. Whereas the lightest one was by no NPK Pelangi fertilizer application treatment (n0) with only 120,83 g per crop; (2) the Grow Team M foliar spray concentration affected very significantly on the plant height at 2, 4, and 6 weeks after sowing, days of crop firstly flowered, days of crop harvested, number of fruit per crop, weight per fruit, and fruit weight per crop. The weighest fruit was attained by 2 ml per litre water treatment (d2), namely 192,50 g per crop and the lightest one was by no Grow Team M foliar spray fertilizer application treatment (d0) with only 159,17 g per crop; and (3) the interaction between those two factors affected significant until very significantly on the plant height at 2, 4, and 6 weeks after sowing and number of fruit per crop, but it did not give significant on the days of crop firstly flowered, days of crop harvested, weight per fruit, and fruit weight per crop.